Group portrait of the attendees of the 1959 Monte Toyon A at Monte Toyon in Aptos, California - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing the attendees of the Monte Toyon A meeting, held July 18-25, 1959 at Monte Toyon in Aptos, California.